Hierarchical structure-and-motion recovery from uncalibrated images - Toldo, Roberto; Gherardi, Riccardo; Farenzena, Michela; Fusiello, Andrea (Computer vision and image understanding, 2015)
•We describe a hierarchical structure-from-motion pipeline.•No information is needed beside images themselves.•The pipeline proved successful in real-world tasks. This paper addresses the structure-and-motion problem, that requires to find camera motion and 3D structure from point matches. A new pipeline, dubbed Samantha, is presented, that departs from the prevailing sequential paradigm and embraces instead a hierarchical approach. This method has several advantages, like a provably lower computational complexity, which is necessary to achieve true scalability, and better error containment, leading to more stability and less drift. Moreover, a practical autocalibration procedure allows to process images without ancillary information. Experiments with real data assess the accuracy and the computational efficiency of the method.